Pengaruh Work-Life Balance Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Mediasi - Wirtadipura, Dian; Sumarjo, Wahid (Lembaga Pengembangan Kinerja Dosen, 2025)
Work-life balance has become an important issue in human resource management, mainly because of its impact on employee satisfaction and performance. This study examines the influence of work-life balance on employee performance, with job satisfaction as a mediating variable. This study uses a causal approach with 115 employees at PT. Biotis Agrindo. The data was analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The study results show that work-life balance has a positive and significant effect on job satisfaction and employee performance, both directly and indirectly through job satisfaction. These findings confirm that job satisfaction mediates the relationship between WLB and performance, reinforcing the social exchange theory that perceptions of fair treatment from organisations will be reciprocated with positive work behaviours. The practical implication of this research is that organisations need to implement work policies that support work-life balance as part of performance improvement strategies.